PENDIDIKAN PROFETIK PESANTREN ROHMATUL UMAM BANTUL PADA REMAJA DI ERA REVOLUSI INDUSTRI 4.0 - Muhammad Nur Adnan Saputra (Edudeena : Journal of Islamic Religious Education, 2020)
Abstract: Islamic boarding schools are at the forefront of instilling prophetic values. In an era where human jobs are replaced by machines, pesantren will still be responsible for maintaining the morals of this nation's generation. One of the pesantren that has made innovations in instilling prophetic values is the Rohamatul Umam Kretek Bantul Islamic boarding school. Teenage students are directly educated by the Kyai with a wide and deep variety of religious knowledge, then the students share religious knowledge with children and adolescents in a mosque not far from the pesantren. In Islamic Personal Development activities, students are given the freedom to use methods when teaching Islamic religious knowledge. The right method can make the atmosphere of the activity fun and the material presented can be well received by the youth around the boarding school. The Rohmatul Umam Islamic boarding school instills Islamic values, the role of the prophet through the figure of a Kyai. Rohmatul Umam Islamic boarding school in providing prophetic values cannot be separated from three pillars, namely: first, calling for good can be translated into the spirit of fighting for humanity (humanization), second, preventing what is wrong, can be translated with the spirit of rejecting all forms of oppression (liberation), third, faith in Allah can be translated into the spirit of perennial philosophy (transcendence). Become a teenager with an Islamic personality full of confidence, so that he can be skilled in facing changes in the revolutionary era. Abstrak: Pesantren berada di garda terdepan dalam menanamkan nilai-nilai profetik. Di era di mana pekerjaan manusia digantikan oleh mesin, pesantren akan tetap bertanggung jawab menjaga moral generasi bangsa ini. Salah satu pesantren yang melakukan inovasi dalam menanamkan nilai-nilai profetik adalah Pesantren Rohamatul Umam Kretek Bantul. Pelajar remaja dididik langsung oleh Kyai dengan ragam ilmu agama yang luas dan mendalam, kemudian para santri berbagi ilmu agama dengan anak-anak dan remaja di sebuah masjid yang tidak jauh dari pesantren. Dalam kegiatan Islamic Personal Development, siswa diberikan kebebasan untuk menggunakan metode dalam mengajarkan ilmu agama Islam. Metode yang tepat dapat membuat suasana kegiatan menjadi menyenangkan dan materi yang disampaikan dapat diterima dengan baik oleh para remaja di sekitar pondok pesantren. Pesantren Rohmatul Umam menanamkan nilai-nilai Islam, peran nabi melalui sosok seorang Kyai. Pesantren Rohmatul Umam dalam memberikan nilai-nilai kenabian tidak lepas dari tiga pilar, yaitu: pertama, menyeru kepada kebaikan dapat diterjemahkan ke dalam semangat memperjuangkan kemanusiaan (humanisasi), kedua, mencegah yang salah, dapat diterjemahkan dengan semangat. menolak segala bentuk penindasan (pembebasan), ketiga, iman kepada Allah dapat diterjemahkan ke dalam semangat filsafat abadi (transendensi). Menjadi remaja berkepribadian Islami yang penuh percaya diri, sehingga mampu terampil menghadapi perubahan di era revolusi.